The Impact of Freeze‐Thaw History on Soil Carbon Response to Experimental Freeze‐Thaw Cycles. Issue 5 (20th May 2022) - Rooney, Erin C.; Bailey, Vanessa L.; Patel, Kaizad F.; Possinger, Angela R.; Gallo, Adrian C.; Bergmann, Maya; SanClements, Michael; Lybrand, Rebecca A.
Abstract: Freeze‐thaw is a disturbance process in cold regions where permafrost soils are becoming vulnerable to temperature fluctuations above 0°C. Freeze‐thaw alters soil physical and biogeochemical properties with implications for carbon persistence and emissions in Arctic landscapes. We examined whether different freeze‐thaw histories in two soil systems led to contrasting biogeochemical responses under a laboratory‐controlled freeze‐thaw incubation. We investigated controls on carbon composition through Fourier‐transform ion cyclotron resonance mass spectrometry (FT‐ICR‐MS) to identify nominal carbon oxidation states and relative abundances of aliphatic‐type carbon molecules in both surface and subsurface soils. Soil cores (∼60 cm‐depth) were sampled from two sites in Alaskan permafrost landscapes with different in situ freeze‐thaw characteristics: Healy (>40 freeze‐thaw cycles annually) and Toolik (<15 freeze‐thaw cycles annually). FT‐ICR‐MS was coupled with in situ temperature data and soil properties (i.e., soil texture, mineralogy) to assess (a) differences in soil organic matter composition associated with previous freeze‐thaw history and (b) sensitivity to experimental freeze‐thaw in the extracted cores. Control (freeze‐only) samples showed greater carbon oxidation in Healy soils compared with Toolik, even in lower mineral horizons where freeze‐thaw history was comparable across both sites. Healy showed the most loss of carbon compounds following experimental freeze‐thaw in the lower mineral depths, including a decrease in aliphatics. Toolik soils responded more slowly to freeze‐thaw as shown by intermediary carbon oxidation distributed across multiple carbon compound classes. Variations in the response of permafrost carbon chemistry to freeze‐thaw is an important factor for predicting changes in soil function as permafrost thaws in high northern latitudes. Plain Language Summary: As global warming progresses, permafrost (soils frozen for two or more consecutive years) is undergoing thaw. However, the process of permafrost thaw is more than a simple transition from frozen to thawed. Instead, thawing permafrost undergoes repeated freeze‐thaw cycles on an annual, seasonal, and daily basis. Freeze‐thaw cycles impact soils by changing soil nutrient availability and biological activity with implications for carbon decomposition. We investigated two types of freeze‐thaw response: (a) how previous freeze‐thaw history influenced current soil function and (b) how soils responded to experimental freeze‐thaw. We tested both types of soil response to freeze‐thaw cycles by evaluating the chemical composition of soil carbon. We found that soil response to freeze‐thaw differed by site, even in the lower soil depths with little exposure to prior freeze‐thaw. Our findings indicate that as permafrost thaws and begins to undergo freeze‐thaw cycles, the response to those freeze‐thaw cycles may differ by site. Variation in soil response could play a crucial role in predicting greenhouse gas emissions and rates of emission from thawing Arctic landscapes. Key Points: A combination of freeze‐thaw history and soil properties dictated soil response to experimental freeze‐thaw cycles The two soils with the least prior freeze‐thaw showed diverging responses to freeze‐thaw, likely due to soil moisture and mineralogy Future increases in freeze‐thaw in both the active layer and thawing permafrost may result in contrasting carbon responses across sites